Climate Change Risks to the Maize Value Chain in Ethiopia: Proactive Actions for Resilience in the Ethiopian Food System Resilience Program Districts - International Maize and Wheat Improvement Center (International Maize and Wheat Improvement Center, 2024)
Maize is the most productive and one of the leading economically important cereal crops in Ethiopia. However, its benefits are found to be compromised by current and future risks associated with climate change and variability. The outlined climate change impacts are expected to be witnessed across maize-growing areas. • By 2035, Belg rainfall is projected to increase in some FSRP districts while decreases in others. The changes range from - 47 to 21 mm and its variability lies between 9 and 42%. • Meher rainfall will increase in most FSRP districts, and the changes range from –8 to 189 mm, and changes in its variability lie between –1 and 29%. • During Meher season, the average daily maximum temperature (Tmax) will increase by 0.84-1.390C while the average daily minimum temperature (Tmin) will increase by 1.13-1.520C . During Belg, Tmax will increase by 1.12-1.420C while Tmin will increase by 1.41-1.730C across maize-producing FSRP districts. • General tendencies of more extreme rainfall and wetness in both seasons are projected. • Hot days and hot nights will increase, and diurnal temperature ranges will shrink. • About 10 - 50% of maize growing areas have been affected by high drought conditions during the recent past. Shifts in major climatic variables in space and time will affect maize production and marketing, followed by several unwelcomed socio-economic consequences.